Transparent farm based on blockchain technology - Xiujuan WANG; Jing HUA; Mengzhen KANG; Haoyu WANG; Yong YUAN; Fei-Yue WANG (智能科学与技术学报)
With the development of new types of agricultural business mode,consumers can send orders remotely to the growers,in order to satisfy their high requirements for the safety of agricultural products.In addition to consumers and growers,stakeholders of agricultural supply chain include farm managers,agricultural input suppliers,agricultural knowledge suppliers and third-party regulators and financial service providers.Therefore,how to build a trustworthy community,to protect the benefit of all parties and achieve sustainable development are challenges that are faced by new farming business mode.For farm managing mode with multiple stakeholders,smart contracts provide a credit guarantee mechanism.An online farm platform based on smart contracts,which constructs a trustworthy community corresponding to the offline one with blockchain technology was proposed in this paper.Differing from traditional traceability systems,the characteristics of the decentralized data management and non-tamper ability were utilized,and the authenticity of data through the mutual verification could be ensured.These methods increase the cost of data fraud,and thus achieve a trustworthy agricultural community.This work aims at ensuring the data validity in Internet+ agriculture,and supporting the orderly sustainable development of emerging agricultural management mode.